PENDAMPINGAN PENYUSUNAN RANCANGAN PERATURAN DESA (RANPERDES) DI DESA BONTULA KECAMATAN ASPARAGA KABUPATEN GORONTALO - Junus, Dikson; Nuna, Muten; Hiola, Abdul Samad; Podungge, Abdul Wahab; Napir, Suaib; Hunawa, Robby; Sahi, Nirmala A.; Arsjad, Muh Fachri; Tabo, Sarfan; Walahe, Dewi; Harun, Nur Istiyan; Polinggapo, Jefri; Pauweni, Lisnawaty; Puspaningrum, Dian; Hatta, Herman (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2025)
This activity is a form of Community Service (PKM) which aims to open the horizons and insights of the community regarding the Draft Village Regulation as an important part of better village governance. The methods used in this mentoring activity include activity planning, activity preparation, activity implementation and discussion in the form of village deliberation meetings accompanied by dialogues that allow participants to explore as much knowledge as possible and find solutions to the problems of drafting village regulations faced. The results achieved in the mentoring activity for drafting Village Regulations carried out in Bontula Village, Asparaga District, namely where the activity ran smoothly and without any significant obstacles, both from the planning stage to the village deliberation. The smooth running of the activity was due to the support of all stakeholders in helping the Community Service team to carry out mentoring activities optimally. In this activity, the resource person not only delivered material related to the urgency of drafting Village Regulations in the implementation of village government, but also the technicalities of drafting Village Regulations accompanied by simulations that were focused and easy to understand by participants, so that participants in this activity could understand the theory and practice of drafting Village Regulations in accordance with applicable laws and regulations. The knowledge gained by participants in this activity is expected to be a strong foundation for producing quality Village Regulations, especially in Bontula Village, Asparaga District, Gorontalo Regency.Keywords : Mentoring, Drafting, Draft Village Regulations